2019
DOI: 10.3390/brainsci9110313
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive Compulsive Symptoms and Psychopathological Profile in Children and Adolescents with KBG Syndrome

Abstract: KBG syndrome is a rare multisystem developmental disorder caused by ankyrin repeat domain-containing protein 11 (ANKRD11) gene haploinsufficiency, resulting from either intragenic loss-of-function mutations or microdeletions encompassing the gene. Concerning the behavioral phenotype, a limited amount of research has been focused on attention deficit and hyperactivity disorder, autistic-like features, anxiety and impairments in emotion regulation, and no study has provided a systematic assessment. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…It seems warranted to conduct in the future quantitative studies, with rating scales, as part of a longitudinal natural history study, as a way to really elaborate what ASD symptoms manifest in KBG syndrome, independent of the intellectual disability. However, from an overall psychiatric perspective, eighty percent had behavioral abnormalities, including aggressive and violent behavior, impulsivity, or repetitive compulsive behavior, consistent with what has been previously reported [33].…”
Section: Discussionsupporting
confidence: 84%
“…It seems warranted to conduct in the future quantitative studies, with rating scales, as part of a longitudinal natural history study, as a way to really elaborate what ASD symptoms manifest in KBG syndrome, independent of the intellectual disability. However, from an overall psychiatric perspective, eighty percent had behavioral abnormalities, including aggressive and violent behavior, impulsivity, or repetitive compulsive behavior, consistent with what has been previously reported [33].…”
Section: Discussionsupporting
confidence: 84%
“…Participants were recruited at the Child and Adolescent Psychiatry Units of Bambino Gesù Hospital and Policlinico Universitario Agostino Gemelli in Rome. Fifteen participants had already enrolled in a previous related study [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Haploinsufficiency of ANKRD11 due to microdeletion of chromosome 16q24.3 or loss of function mutation in the ANKRD11 gene results in the KBG syndrome phenotype, which includes neurodevelopmental problems. Alfieri et al reported a low mean TIQ score (66.0 ± 16.2, represented as mean ± SD) in 17 patients with KBG syndrome ( Alfieri et al, 2019 ), and van Dongen et al (2017) showed similar mean TIQ distribution (66.5 ± 15.6 in 12 children, 62.5 ± 7.1 in 6 adults). As mentioned above, most patients have moderate to mild ID and more than half of the adults with KBG syndrome have jobs and are self-sufficient in ordinary life ( Goldenberg et al, 2016 ; Low et al, 2016 ).…”
Section: Resultsmentioning
confidence: 98%
“…In addition to ID, some behavioral and psychopathologic problems such as ADHD, autism-like features, and impulsivity are major issues in patients with KBG syndrome ( Novara et al, 2017 ). In recent study of 17 pediatric patients with KBG syndrome, there was a higher prevalence of obsessive-compulsive traits, tic disorders, depressive mood, and ADHD as compared with the general population; obsessive-compulsive traits, in particular, did not seem to be related to cognitive level ( Alfieri et al, 2019 ). Similarly, another study also mentioned that ADHD-like behavioral problems associated with KBG syndrome could not be directly related or explained with a specific intelligence profile ( van Dongen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%